(untitled) (Journal of the College of Languages (JCL), 2022)
Political Discourse Analysis is an important linguistic study approach used by politicians to gain people support. The present paper sheds light on the figures of speech of emphasis in the televised debate between the two presidential elections candidates, Emmanuel Macron and Marine Le Pen and the distinctive effect they add to the political discourse to win general public support as well as the presidential elections. The present paper provides a rudimentary definition and an analysis of the terms “discourse” and “political discourse” and traces the significant role played by politically directed televised Media and internet to support political parties through broadcasting political events. Through conducting an analytical study, the paper considers the discourse analysis concept that aims at deconstructing the speech modules to attain the required speech purpose. Part of the present study theoretical approach, the paper terms and clarifies all types of Figures of speech used by politicians to create a publically stronger luminous witty and emotional impact. As for the paper practical approach, it sheds light on the stressing effect of four types figure of emphasis in French and the impact created on the political discourse. Thus, it can be remarked that both candidates particularly Macron has made use of the figures of speech in his political discourse, specifically after winning the presidential elections. Pun or paronomasia, repetition and accumulation in comparison with redundancy are impressively used in Macron’s political discourse to win public support. Résumé L’analyse du discours politique a un écho large dans les études linguistiques. Les politiciens essayaient d’utiliser le langage pour attirer l’attention de leur public à leurs décisions. Dans cette recherche, nous parlons du rôle des figures d’insistance entre les deux candidats aux élections présidentielles, Emmanuel Macron et Marine Le Pen. Notre mission est de découvrir l’impact de ces figures dont les candidats ont profité afin de gagner les élections. Ces figures donnent au texte une expression particulière dans le but de convaincre les gens. De plus, nous définissons en générale le terme «discours» en expliquant l’analyse du discours politique, puis nous montrons l’effet des médias sur la politique en transmettant les événements selon l’intérêt du politicien qui les soutient. Ensuite, nous abordons le concept d’analyse du discours et son objectif de déconstruire les éléments essentiels du discours en menant une étude analytique. Sa tâche principale est de séparer les facteurs qui forment la parole afin d’atteindre le but du discours. En ce qui concerne le cadre théorique, nous étudions quatre types de figures d’insistance et leur effet de renforcer le texte qui se base en premier lieu sur le style et la capacité d’utiliser les méthodes rhétoriques. Enfin, nous trouvons que les deux candidats profitent des figures d’insistance et surtout Macron après avoir remporté les élections. Nous constatons que l’anaphore, la répétition et l’accumulation sont plus utilisés que la redondance.